Groundwater Drought and Cycles in Xuchang City, China - Huang, Jia; Cao, Lianhai; Yu, Furong; Liu, Xiaobo; Wang, Lei (Frontiers in Earth Science, 2021)
The urban groundwater system is complex and affected by the interaction of natural and human factors. Groundwater scarcity can no longer reflect this complex situation, and the concept of groundwater drought can better interpret this situation. The groundwater drought cycle is the time interval in which groundwater droughts occur repeatedly and twice in a row. The study of the groundwater drought cycle can more comprehensively grasp the development characteristics of the groundwater drought, which is of great importance for the development, utilization and protection of groundwater. This study used monthly observation data from seven groundwater wells in Xuchang, China, in the period 1980–2018. We applied the Kolmogorov-Smirnov test to select the best fitting distribution function and constructed a standard groundwater index (SGI). We analyzed groundwater drought at different time scales and used Morlet’s continuous complex wavelet transform to analyze the groundwater drought cycles. The following results were obtained: (1) the maximum intensity of groundwater drought in the seven observation wells ranged from 104.40 to 187.10. Well-3# has the most severe groundwater drought; (2) the drought years of well–5# were concentrated in 1984–1987 and 2003–2012, and those in the other wells in 1994–1999 and 2014–2018; and (3) the groundwater drought cycles in the seven observation wells were 97–120 months，and the average period is about 110 months. The cycle length had the following order: well–7# > well–4# > well–5# > well–2# > well–1# > well–3# > well–6. Therefore, Morlet wavelet transform analysis can be used to study the groundwater drought cycles, and can be more intuitive in understanding the development of regional groundwater droughts. In addition, through the study of the Xuchang groundwater drought and its cycle, the groundwater drought in Xuchang City has been revealed, which can help local relevant departments to provide technical support and a scientific basis for the development, utilization and protection of groundwater in the region.